Psicanálise, sedimentação e deriva: reflexões sobre os movimentos de uma História real - Pinto, Osmar Luvison (Revista de História, 1996)
This article studies about some inner characteristics of the human being, regarded as object of study of psychoanalysts and professionals in the field of Human Sciences. Man's inner side from a psychoanalytical viewpoint is a structure constituted of continuous movements. The researcher is required to have a methodological flexibility - an attitude before the phenomenum that can include the instabilities of both the researcher and the patient. When developing the psychoanalytical method, Freud tried to take into account the relations between the patient's and the analyst's inner realities. This paper reports part of this story, suggesting that the psychoanalytical method is a useful reference for researchers in other fields.